Case and Grammatical Relations : Studies in Honor of Bernard Comrie - Comrie, Bernard, 1947-; Corbett, Greville G.; Noonan, Michael (Michael P.) (Typological studies in language ;, 2008)
The papers in this volume can be grouped into two broad, overlapping classes: those dealing primarily with case and those dealing primarily with grammatical relations. With regard to case, topics include descriptions of the case systems of two Caucasian languages, the problems of determining how many cases Russian has and whether Hungarian has a case system at all, the issue of case-combining, the retention of the dative in Swedish dialects, and genitive objects in the languages of Europe. With regard to grammatical relations, topics include the order of obliques in OV and VO languages, the ef.